An analysis of theta role of verbs in Hausa / Ali Umar Muhammad - Muhammad, Ali Umar (2014)
Hausa is a native language of an ethnic group who call themselves Hausawa. The Hausas are basically the dominant ethnic group in an area known as the Hausa land in Nigeria, some part of Niger, and other African countries. It is evident that various researchers have provided some extensive descriptions of the grammar of the language, but thematic relation, which is one of the important theories in syntax within Generative Grammar, appeared to be neglected, as none of the available literature discussed the theta role using Radford‟s theory. Theta role is precisely the semantic relationship between the verb and arguments. The study was concerned with developing a structural knowledge in the syntactical studies with special emphasis on analyzing the thematic roles in Hausa sentences. It described Hausa sentences and it constituent by examining the possibility of applying the principle of theta criteria in Hausa sentence structure with a view to better understanding of the concept of thematic role and it application. The study went further to investigate the relationship between thematic roles and arguments structure of verbs found in the language. However, the analysis involved the explanation of Hausa verb, its types and function in relation with the arguments or participants in the phrases, clauses, and sentences. The data of this study was collected through interview which has been conducted to a Hausa native speaker, Radford (2009) theory of thematic relation used as a theoretical framework as well as analytical framework. The findings show that the thematic roles provide valuable information in knowing the number of arguments that are required by a particular verb. From the analysis, the result show that the entire theta role presented in Radford (2009) and many more have been found from the data, the theta role of Agent is the most common and frequent role in the data. The analysis shows that theta role exists in some sentential constructions with zero verbs.